Observer-Based Sliding Mode Control for Vehicle Way-Point Tracking with Unknown Disturbances and Obstacles - Jiacheng Song; Mingjie Shen; Yanan Zhang (Actuators)
In this paper, an advanced vehicle way-point tracking control method, including kinematic control, dynamic control and an obstacle avoidance strategy, is introduced. In the kinematic part, a vehicle kinematic model is established, along with the coordinate transformation between the vehicle and its target. A way-point tracking control law is developed to optimize the vehicle’s movement along predefined way-points. In the dynamic part, a dynamic model considering the actual disturbances and losses is established. An observer compensation technique is utilized to monitor and mitigate disturbances, while sliding mode control, enhanced by a HyperSpiral algorithm, ensures accurate and stable tracking performance. Furthermore, to tackle real-world path planning challenges, an improved way-point tracking obstacle-avoidance algorithm is developed to generate effective way-points for navigating around obstacles. Finally, simulation results validate that the vehicle consistently tracks target way-points in complex scenarios, highlighting the robustness and effectiveness of the proposed method.